IbM UKGS (USAHA KESEHATAN GIGI SEKOLAH) SEKOLAH DASAR - Astuti, Lilies Anggarwati; Mokhtar, Shulhana (Jurnal BALIRESO, 2018)
Specific objectives to be achieved are giving birth to independent young dentists who are aware ofthe importance of maintaining oral and dental health in the form of UKGS improvement. In SouthSulawesi in particular, public awareness of the importance of dental and oral health still needs tobe improved. On this basis, he wants to try to offer a product development of Human Resources(HR) in the field of dentistry. The method used in achieving this goal is to complete UKGSfacilities and infrastructure. It can make students as pioneers in the implementation of dental andoral health degrees and the development of UKGS and UKS in their schools, making schools aspilot schools that develop UKGS. Target and outcome: 1) The birth of a cadre of young dentistsand young doctors. 2) Increased knowledge of cadres of young dentists and young doctors. 3)Increasing the degree of dental and oral health which is reflected in healthy living behavior. 4)Products "UKGS and UKS Utilization Module" for all elementary school residents. 5) Certificateof training for young dentists and young doctors for students and teachers. 6) Final reportspublished through scientific publications on accredited journals after dedication.